2023
DOI: 10.1002/ejoc.202300058
|View full text |Cite
|
Sign up to set email alerts
|

HFO‐1234yf as a CF3 Building Block: Synthesis of Trifluoromethyl Quinoline and Chromene Derivatives from Trifluoromethyl‐ynones

Abstract: Trifluoromethyl ynones derived from the refrigerant gas HFO-1234yf (2,3,3,3-tetrafluoropropene) react with nucleophiles via a Michael-type addition process and the allenolate intermediate formed reacts intramolecularly with a carbonyl group to form heterocyclic derivatives. Thus, reaction of 2-amino and 2hydroxyl benzaldehyde or ketone substrates with trifluoromethyl ynone derivatives gives trifluoromethyl quinoline and chromene products by a one-pot tandem ring closing sequence, forming pharmaceutically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…To gain insight into the reaction mechanism, various mechanistic experiments were performed, 21 and we proposed the reaction control experiment, as shown in Scheme 3. Firstly, we verified the final structure of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insight into the reaction mechanism, various mechanistic experiments were performed, 21 and we proposed the reaction control experiment, as shown in Scheme 3. Firstly, we verified the final structure of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In 2023, Brittain et al 31 showed that trifluoromethyl ynones obtained from a refrigerant gas feedstock (HFO-1234yf ) can be easily transformed into various substituted Organic & Biomolecular Chemistry Review a nucleophilic reagent. The resulting allenolate intermediate then undergoes an intramolecular reaction to produce CF 3heterocyclic derivatives.…”
Section: 33-trifluoropropene Derivativesmentioning
confidence: 99%